The Influence of Employer Branding on Millennial Employee Interest and Retention in Technology Companies - Claudia Pereira Soares; Pudji Astuty (Jurnal Multidisiplin Indonesia, 2025)
This study examines the influence of employer branding on millennial employee interest and retention in technology companies. The millennial generation, born between 1981-1996, now dominates the global workforce with a 35% proportion in 2024, while the technology sector experiences employee turnover rates of up to 13.2% annually. The research employed a quantitative method with surveys of 385 millennial employees from 15 technology companies in Jakarta and Bandung. Results indicate that employer branding significantly influences millennial work interest with a coefficient of determination R² = 0.742, and employee retention with R² = 0.689. The dimensions of compensation and benefits (β = 0.324), positive work environment (β = 0.298), and career development opportunities (β = 0.267) emerged as the most influential factors. Companies with strong employer branding demonstrated 78% higher retention rates compared to those with weak branding. These findings provide practical implications for technology company management to optimize employer branding strategies in attracting and retaining millennial talent.